2002
DOI: 10.1002/sia.1456
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved microchemical analysis of chromate‐conversion‐coated aluminum alloy AA2024‐T3

Abstract: The corrosion of aerospace aluminum alloys has been linked to the electrochemical behavior and chemical composition of constituent intermetallic compounds (IMCs). In this study, secondary ion mass spectrometry (SIMS), x-ray photoelectron spectroscopy (XPS), synchrotron infrared microspectrometry (SIRMS) and xray absorption near-edge structure spectroscopy (XANES) were used to characterize chromate conversion coatings (CCCs) formed on AA2024-T3 sheet and cast IMC analogs. The nascent surface film formed on IMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In general, micro-chemical analysis combined with large area surface-sensitive spectroscopies and imaging, has proved to be essential for understanding the mechanisms controlling processing-performance relationships [19]. Figure 3 shows a side view of the source filament.…”
Section: Laser Confocal Microscopymentioning
confidence: 99%
“…In general, micro-chemical analysis combined with large area surface-sensitive spectroscopies and imaging, has proved to be essential for understanding the mechanisms controlling processing-performance relationships [19]. Figure 3 shows a side view of the source filament.…”
Section: Laser Confocal Microscopymentioning
confidence: 99%
“…Since the reduction reaction of chromate is fast and exposure time is longer than that reported in Clark's work [60], the film may also involve the polymerization of Cr III on the monolayer [29], leading to a large thickness. It is also expected that the film thickness on each IMC would be different, which requires advanced surface techniques to characterise as studied in [30,31], and is not the focus of this work. The thickness of chromate film is roughly estimated using the measured capacitance in this work.…”
Section: Capacitance Characteristics Of Imcs and Al-4cu In 01 M Naclmentioning
confidence: 99%
“…However, corrosion associated with the secondary phase particles is strongly supressed by the addition of chromate to the solution, which leads to the formation of a compact Cr III -Cr VI mixed hydroxide film [26][27][28]. The protective film is composed of chemisorbed Cr III oxides and adsorbed Cr VI oxides [29], and is chemically and topographically heterogeneous on the surface [30,31]. The thickness of the film on the AA2024 matrix and Al 20 Cu 2 Mn 3 particles are larger than that on Al 2 Cu and S-phase [31].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial aluminumÀcopper alloy AA2024-T3, primarily used in aircraft in the form of sheet and fuselage and plate for the lower wing, contains several alloying elements that lead to the formation of a complex, multiphase structure ( Figure 15.1). Cu, Mg, Mn, Si, and Fe are present in AA2024-T3 in appreciable amounts and form intermetallic compounds (IMCs) of composition Al 2 Cu, Al 2 CuMg, Al 2 Cu 2 Fe, Al 7 Cu 2 Fe, Al 12 Si(FeMn) 3 , Al 20 Cu 2 (MnFe) 3 , and Al 20 Cu 3 Mn 3 . These secondary phase precipitates and IMCs enhance the mechanical strength of the alloy.…”
Section: Aqueousmentioning
confidence: 99%
“…However, it has been shown that the presence of IMCs strongly affects both the thickness and the surface morphology of CCC formed on AA2024-T3. 3 The application and corrosion-inhibiting mechanisms of these coatings will be discussed in some more detail in the following sections.…”
Section: Aqueousmentioning
confidence: 99%